Moral Responses to the COVID-19 Crisis - Navajas Ahumada, Joaquin Mariano (2021)
The COVID-19 pandemic has raised complex moral dilemmas that have been the subject of extensive public debate. Here, we study how people judge a set of controversial actions related to the crisis: relaxing data privacy standards to allow public control of the pandemic, forbidding public gatherings, denouncing a friend who violated COVID-19 protocols, prioritizing younger over older patients when medical resources are scarce, and reducing animal rights to accelerate vaccine development. We collected acceptability judgements in an initial large-scale study with participants from 10 Latin American countries (N = 15 420). A formal analysis of the intrinsic correlations between responses to different dilemmas revealed that judgements were organized in two dimensions: one that reflects a focus on human life expectancy and one that cares about the health of all sentient lives in an equitable manner. These stereotyped patterns of responses were stronger in people who endorsed utilitarian decisions in a standardized scale. A second pre-registered study performed in the USA (N = 1300) confirmed the replicability of these findings. Finally, we show how the prioritization of public health correlated with several contextual, personality and demographic factors. Overall, this research sheds light on the relationship between utilitarian decision-making and moral responses to the COVID-19 crisis.